The friendly incidental portal vein thrombus in liver transplantation. Issue 7 (July 2015) - Koh, Peng Soon; Chan, See Ching; Chok, Kenneth Siu‐Ho; Sharr, William Wei; Wong, Tiffany Cho-Lam; Sin, Sui Ling; Lo, Chung Mau
<x xml:space="preserve">Abstract</x> Improved outcomes have been shown in liver transplantation (LT) with portal vein thrombosis (PVT). However, PVT is still discovered incidentally during surgery despite careful preoperative imaging. Data are limited comparing the outcomes of incidental PVT with PVT diagnosed via preoperative imaging before LT. This study aims to compare the overall outcomes of patients with PVT. From 2008 to 2012, 369 patients had LT, and 58 patients with PVT were identified. They were divided into those with non‐PVT (group 0; n = 311), preoperatively identified PVT (group 1; n = 28), and incidental PVT (group 2; n = 30). The demographics, characteristics, preoperative assessment, and postoperative outcomes were compared. A survival analysis was also performed. Baseline characteristics and preoperative evaluations of all 3 groups were comparable (P > 0.05) except for Model for End‐Stage Liver Disease score, tumor status, platelet levels, and serum bilirubin. A multivariate analysis only showed a high serum bilirubin level to be a predictor of PVT (P = 0.004; odds ratio, 3.395; 95% confidence interval, 1.467‐7.861). Postoperative outcomes were also comparable (P > 0.05). Compared to group 2, group 1 had more patients with a Yerdel classification of 3 or 4 with more extensive surgical intervention required (P = 0.02). The survival analysis in all 3 groups was comparable with 5‐year survival rate of 87.4%, 84.6%, and 91.8% in group 0, 1, and 2, respectively (P = 0.66). In conclusion, recipients with PVT undergoing LT can have similar outcomes as the non‐PVT patients even if PVTs were discovered incidentally. Discovery of incidental PVT only requires thrombectomy with no substantial change of treatment strategy, and the outcome is not adversely affected because most incidental PVTs are of a lower Yerdel grade. Preoperative imaging is useful to identify those with a higher Yerdel grade to allow planning of surgical strategy during transplantation. Liver Transpl 21:944‐952, 2015. © 2015 AASLD.